Evaluating the impact of point‐ of‐care decision support tools in improving diagnosis of obese children in primary care1. (16th April 2013) - Ayash, Christine R.; Simon, Steven R.; Marshall, Richard; Kasper, Jill; Chomitz, Virginia; Hacker, Karen; Kleinman, Ken P.; Taveras, Elsie M.
Abstract Objective: The purpose of this quasi‐experimental study was to examine the effect of a computerized point‐of‐care alert with clinical decision support on the rates of diagnosis of childhood obesity in a multisite group practice in Massachusetts; Cambridge Health Alliance (CHA) which implemented an alert, relative to a separate group practice, Harvard Vanguard Medical Associates (HVMA), that did not. Design and Methods: Height and weight data from 19, 466 children of 2‐18 years with 34, 908 well‐child care visits in CHA and 123, 446 children with 282, 271 visits in HVMA between 2006 and 2008 were collected. The alert and decision support tool was activated for CHA patients with an age‐ and sex‐specific body mass index of ≥95th percentile. The main outcome measure was documentation of an International Classification of Diseases, Ninth Revision [ICD‐9] code for obesity before and after implementation of the alert at CHA in 2007. Results: Among obese children, the adjusted rate of an ICD‐9 diagnosis of obesity increased from 2006‐2007 to 2008 significantly more at CHA than at HVMA (P < 0.001 for time‐by‐provider group interaction). In 2006‐2007, the rate of ICD‐9 diagnosis of obesity was significantly lower at CHA than at HVMA (adjusted odds ratio [OR]: 0.57; 95% confidence interval [CI]: 0.52‐0.62); but by 2008 was significantly higher at CHA than HVMA (adjusted OR: 1.25; 95% CI: 1.14‐1.38). Conclusion: A point‐of‐care alert was effective in improving obesity diagnosis in a multisite group practice, relative to a separate group practice that did not adopt an alert. Clinical decision support tools could help improve obesity diagnosis in pediatric primary care.